KEPASTIAN HUKUM PENJATUHAN REHABILITASI MEDIS DALAM TINDAK PIDANA NARKOTIKA (STUDI TERHADAP PUTUSAN MAHKAMAH AGUNG NOMOR 26/PID.SUS/2019/PN.PTI DAN PUTUSAN MAHKAMAH AGUNG NOMOR 378/PID.SUS/2017/PN.SMN) - Jennifer Jennifer (Fakultas Hukum Universitas Tarumanagara, 2021)
Rule of Law reflects a state’s quality. Rule of Law should play an active role in legal disputes. In actuality Decision of the Supreme Court 26/PID.SUS/2019/PN.PTI and Decision of the Supreme Court 378/PID.SUS/2017/PN.SMN show different verdicts. There are two verdicts – rehabilitation and jail time. From it’s benefits medical rehabilitation is very important for the victim. Rehabilitation is a legal act for narcotics abuse. Victims of narcotics abuse are not criminals but people who are ill physically and mentally. The verdict of rehabilitation is more suitable than the verdicts of jail time. Medical rehabilitation is an attempt done in order to recover, heal, and give mental guidance for victims of narcotics abuse. The practical implementation has been very different from the existing laws. Rule of Law can be done well if the practical implementation is also done well. This can be done through revisions of existing laws. The law enforcement has a no less important role to ensure the implementation of every existing law in the society. As a result, Indonesia will have a good, clear, and firm system of Rule of Law towards every legal problem.